Patentability of Animal Models: India and the Globe - Tejas P. Gosavi, Dr (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTPatents and related issues began to ring a bell in research world years ago. Conceptual and theoretical property including new appliances also never new to pharmaceutical industry. But the tug-o-war between the traditional and modern themes remained as it is. Novel therapeutic application of newly invented procedure or instrument also added to think over again about animal models in pharmacy hub for various purpose of research. Transgenic animal’s patent law ideally entered in to a market in 1987. Although it seems easy but rather it was heavy task to develop such disease models which might have taken a quantity ranging from several to many in terms of time, money and human resources. In India animal models are not yet patentable unlike developed countries. In order to use such animal models they should have a close similarity to human organism which will convey the likeness or replica of the pathological entity and its various medians. Transgenic animal disease models are animals that have been genetically altered to have traits that mimic the symptoms of specific human pathologies. In certain inventions such as AIDS mouse as an animal used lack the receptor and co receptor that allows them to be infected with HIV. The mice were genetically altered to contain the gene for human CD4 promoter upstream of the human CD4 gene and human CKR-5 co-receptor gene. Similarly there are different models such as Alzheimer mouse, oncomouse, and smart mouse were also evolved accordingly.